2021
DOI: 10.1186/s13578-021-00661-x
|View full text |Cite
|
Sign up to set email alerts
|

Current insights into the implications of m6A RNA methylation and autophagy interaction in human diseases

Abstract: Autophagy is a conserved degradation process crucial to maintaining the primary function of cellular and organismal metabolism. Impaired autophagy could develop numerous diseases, including cancer, cardiomyopathy, neurodegenerative disorders, and aging. N6-methyladenosine (m6A) is the most common RNA modification in eukaryotic cells, and the fate of m6A modified transcripts is controlled by m6A RNA binding proteins. m6A modification influences mRNA alternative splicing, stability, translation, and subcellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…Decreased m 6 A signals were also associated with autophagy induction in our experimental setting, namely 5-azaC post-treatment resulted in diminished pools of m 6 A and elevated levels of LC3B compared to HP stimulation ( Figure 5 C and Figure 6 B). M 6 A RNA modification can also modulate autophagy-mediated anticancer drug resistance [ 50 , 51 ]. Depletion of METTL3, a primary m 6 A methyltransferase, promoted sorafenib resistance in hepatocellular carcinoma (HCC) cells and activated autophagy-associated pathways by limited stability of FOXO3 mRNA under hypoxic conditions [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreased m 6 A signals were also associated with autophagy induction in our experimental setting, namely 5-azaC post-treatment resulted in diminished pools of m 6 A and elevated levels of LC3B compared to HP stimulation ( Figure 5 C and Figure 6 B). M 6 A RNA modification can also modulate autophagy-mediated anticancer drug resistance [ 50 , 51 ]. Depletion of METTL3, a primary m 6 A methyltransferase, promoted sorafenib resistance in hepatocellular carcinoma (HCC) cells and activated autophagy-associated pathways by limited stability of FOXO3 mRNA under hypoxic conditions [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage autophagy seems to have a dual role in atherosclerosis: dysregulated autophagy promotes atherosclerosis, and moderate autophagy inhibits plaque progression ( Zahid et al, 2021 ). Autophagy is a conservative degradation mode of cells, which is essential for maintaining the main functions of cell metabolism ( Chen et al, 2021 ). When cells suffer from nutrient deficiency, oxidative stress, and organelle dysfunction, autophagy degrades unwanted materials through a lysosomal-dependent pathway to maintain cell homeostasis ( Duan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, autophagy currently known includes at least three different pathways: macro-autophagy, micro-autophagy and chaperone mediated autophagy (CMA) (94,95). Among them, the difference among the three mainly lies in the process of binding with lysosomes: macro-autophagy is that cytoplasmic components are directly attached to lysosomes and then directly degraded by lysosomal hydrolases; Micro-autophagy is the invagination of lysosomal membrane, which is engulfed by lysosomes after forming vesicles; CMA enters the lysosome through lysosomal associated membrane protein 2A (LAMP-2A) receptor in the form of complex with the help of chaperone proteins such as Hsc-70 (96,97).…”
Section: M6a Methylation and Autophagymentioning
confidence: 99%
“…M6A methylation can affect the expression of autophagy related genes, regulate autophagy, and play an important role in the occurrence and development of heart failure (97,111,112). It is reported that m6A methylation can inhibit autophagy by affecting the post transcriptional regulation of autophagy related gene 1 (ATG1)/Unc-51-like kinase 1 (ULK1) (113).…”
Section: M6a Methylation and Autophagymentioning
confidence: 99%